Investigating the direct and indirect effects of accounting practices on business information and entrepreneurial growth in the supporting regions of indonesia’s new capital city - La Ode Hasiara; Ahyar Muhammad Diah; Eko Adi Widyanto; L. M. Hasriadi; Rizky Yudaruddin (Cogent Business & Management)
The relocation of Indonesia’s capital to Nusantara Capital City (IKN) is expected to accelerate economic transformation in surrounding regions, particularly Samarinda, Balikpapan, North Penajam Paser, and Paser. This study aims to investigate the direct and indirect effects of accounting system implementation, entrepreneurs’ accounting literacy, availability of financial information, and accounting knowledge on business information and entrepreneurial growth of small and medium enterprises (SMEs) in these regions. Additionally, this study investigates the mediating role of business information in strengthening these relationships. This research employs a quantitative approach using survey data from 725 SMEs in East Kalimantan. The data is analyzed using Partial Least Squares Structural Equation Modeling to test the proposed relationships. The findings reveal that accounting literacy, financial information availability, and accounting knowledge significantly enhance SME growth and sustainability. Moreover, business information acts as a crucial mediator, reinforcing the positive influence of financial management on entrepreneurial success. These results highlight the importance of financial literacy and access to business information in improving SME resilience and competitiveness in rapidly evolving economic environments.